Further Studies on Aggregation of Platelet-Type von Willebrand’s Disease Platelets by Human von Willebrand Factor - Takahashi, H; Tatewaki, W; Hanano, M; Nagayama, R; Shibata, A (Thrombosis and Haemostasis, 1986)
Platelet-type von Willebrand’s disease (vWD) is a bleeding disorder characterized by a heightened interaction between platelets and von Willebrand factor (vWF) as the result of an intrinsic platelet abnormality (probably in GPIb). Platelet aggregability was nearly normal in response to thrombin, wheat germ agglutinin and Ricinus communis agglutinin in this disorder. Unmodified platelets showed no aggregation upon the addition of peanut agglutinin. Partially purified human vWF induced little aggregation of washed patient platelets, but the aggregation was greatly enhanced in the presence of plasma devoid of vWF. Monoclonal antibodies directed against GPIb and GPIIb/IIIa as well as EDTA completely inhibited vWF-induced aggregation. These results indicate that human vWF induces aggregation of platelet-type vWD platelets in the presence of divalent cations and some plasma cofactor(s), and that both GPIb and GPIIb/IIIa are involved in this aggregation.
Keywords: Platelet-type von Willebrand’s disease; von Willebrand factor; Platelet membrane glycoprotein (GP) Ib and GPIIb/IIIa; Receptor; Platelet aggregation